(untitled) (International Journal of Physiotherapy, 2015)
Background: Anterior cervical discectomy and fusion (ACDF) is a commonly performed surgical procedure. However, there is substantial debate regarding the role of physical therapy following this procedure. Therefore, we sought to determine current physical therapy practice following ACDF surgery, as well as determine physical therapists beliefs regarding rehabilitation following ACDF. Methods: One hundred and eighty three licensed Physical Therapists were invited to participate in a descriptive internet based survey; a total of 53 (29%) completed the survey. Physical Therapists were assessed for their current practice, asked to rate the clinical usefulness of various treatment modalities, and indicate their recommendations regarding post-operative physical therapy for subjects following anterior discectomy and fusion. Results were then assessed for frequency distributions, with chi-square analysis for association between demographic data and practice recommendations. Results: The results indicate that Physical Therapists believe patients achieve superior outcomes with the inclusion of post-operative physical therapy, with a low risk of harm. Specific treatments indicated as most useful included endurance exercise (60.4%), isometric strengthening (56.6%), and stretching (45.3%). Other treatment options are discussed in detail. Conclusion: Physical Therapists identified specific activities that they felt were most appropriate for rehabilitation following ACDF surgery. These findings may help to direct both appropriate therapy prescription following ACDF, as well as future research.